2013
DOI: 10.1007/7651_2013_64
|View full text |Cite|
|
Sign up to set email alerts
|

Differentiation of Human Induced Pluripotent Stem Cells into a Keratinocyte Lineage

Abstract: Direct reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) provides an opportunity to develop novel personalized treatment options for numerous diseases and to advance current approaches for cell-based drug discoveries and disease modeling. The ability to differentiate iPSCs into relevant cell types is an important prerequisite for the successful development of iPSC-based treatment and modeling strategies. Here, we describe a protocol for the efficient differentiation of human iPSCs into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 23 publications
(19 reference statements)
0
37
0
1
Order By: Relevance
“…Depending on the application, either skin biopsies, primary cells or cell lines can be used [66,68,69]. Also, human induced pluripotent stem cells provide a source to mimic healthy and diseased skin models as they can be differentiated into keratinocytes [70], fibroblasts [71], melanocytes [72] and endothelial cells [67]. Besides simplified models with dermis and epidermis, also more complex models with hair follicles and adipocytes [73], immune cells [74] and features resembling sweat gland pores [75] exist.…”
Section: Organ-on-a-chipmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the application, either skin biopsies, primary cells or cell lines can be used [66,68,69]. Also, human induced pluripotent stem cells provide a source to mimic healthy and diseased skin models as they can be differentiated into keratinocytes [70], fibroblasts [71], melanocytes [72] and endothelial cells [67]. Besides simplified models with dermis and epidermis, also more complex models with hair follicles and adipocytes [73], immune cells [74] and features resembling sweat gland pores [75] exist.…”
Section: Organ-on-a-chipmentioning
confidence: 99%
“…Nonetheless, it was shown that human iPSC provide a source to mimic healthy skin models as they can be differentiated into keratinocytes [70], fibroblasts [71], melanocytes [72], and endothelial cells [67]. Disease models can be generated with iPSCs derived from somatic cells having a genetic mutation.…”
Section: Outlook: Skin Organoids and Their Potential Use For Personalmentioning
confidence: 99%
“…We previously reported that progenitors of epidermal keratinocytes were generated from human induced pluripotent stem cells (PSCs) (Hayashi et al, , ). In addition, there have been some reports of keratinocyte lineages being induced from mouse (Bilousova & Roop, ) and human (Kogut, Roop, & Bilousova, ) induced PSCs. However, induction of induced PSCs into site‐specific epidermal keratinocytes has not been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Epidermal organotypic “raft” cultures, grown on an air-medium interface, were originally developed in the 1980s as an ex vivo approach for understanding human skin function (Asselineau and Prunieras 1984; Prunieras, Regnier and Woodley 1983) and continue to provide an important alternative to animal models (Getsios, Simpson, Kojima, Harmon, Sheu, Dusek et al 2009). The cultures are typically generated using primary keratinocytes isolated from readily available human foreskins; however, adult keratinocytes and keratinocytes derived from iPS cells (Bilousova and Roop 2013; Kogut, Roop and Bilousova 2014) are emerging as additional cell sources. These isolated keratinocytes can be passaged multiple times in culture and genetically manipulated using viral vectors or RNAi.…”
Section: Introductionmentioning
confidence: 99%